Answer:
A.) g (x) = f (x) - 2
Step-by-step explanation:
The first thing we are going to do in this case is to take into account the following definition.
Translations are transformations that change the position of the graph of a function.
The general shape of the graph of a function is moved up, down, to the right or to the left.
The translations are considered rigid transformations. Now we will see how these are performed.
Vertical translations:
Suppose that k> 0
To graph y = f (x) + k, move the graph of k units up.
To graph y = f (x) -k, move the graph of k units down.
Using the definition we conclude that:
g (x) = f (x) - 4
Answer:
x = 29
y = 13
Step-by-step explanation:
Write 2 equations:
x + y = 42
x - y = 16
Isolate x in the first equation:
x = 42 - y
Substitute this in for x in the second equation:
42 - y - y = 16
42 - 2y = 16
solve for y:
-2y = -26
y = 13
Plug in 13 for y in either equation:
x + 13 = 42
Solve for x:
x = 29
There are 50% chance's that it would land on heads or tails. there could be many different outcomes like (H) for heads and (T) for tails many times like this H, T, H, T, H, T.
Answer:
c- linear units
Step-by-step explanation:
edg :)